Case Report: A Tale of a Cardiac Mass: Looks Like a Papillary Fibroelastoma, Acts Like a Non-bacterial Thromboendocarditis - Ahmad, Ali; Arghami, Arman; El-Am, Edward A.; Foley, Thomas A.; Kurmann, Reto D.; Klarich, Kyle W. (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Benign cardiac tumors and tumorlike conditions are a heterogeneous collection of mass lesions that vary widely in their characteristics, such as presentation, size, and location. In some instances, these tumors are found incidentally, and therefore a broad differential diagnosis should be considered. Case: An elderly male with significant unintentional weight loss and a high risk for cancer presented with an incidental valvular cardiac mass. The mass was thought to be a non-bacterial thromboendocarditis on initial clinical evaluation. After multiple imaging modalities, the mass was suspected to be a papillary fibroelastoma, which was resected due to high stroke risk and multiple previous chronic infarcts on brain MRI. Conclusion: This case highlights the need for a comprehensive cardiac evaluation of a valvular tumor to discern the etiology and rule out other underlying pathophysiological processes that may require alternative interventions to cardiac surgery.